2019
DOI: 10.1021/acs.jpca.8b11877
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Spectra and Structures of Phenyl Isocyanate and Phenyl Isothiocyanate

Abstract: The pure rotational spectra of phenyl isocyanate (PhNCO) and phenyl isothiocyanate (PhNCS) were investigated using Fourier transform microwave (FTMW) spectroscopy in the range from 4 to 26 GHz. For each molecule, rotational transitions due to the parent species and nine minor isotopologues including seven 13 C, one 15 N and one 18 O/ 34 S have been observed in natural abundance. The rm (1) geometries were derived from the resulting sets of rotational constants and are consistent with the equilibrium structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
5
9
1
Order By: Relevance
“…This is consistent with the previously reported geometries of phenyl-NCO and phenyl-NCS which found no differences in the electronic structure of the ring backbone despite the possibility of a change in πdelocalization of the ring with added -NCO or -NCS substituents. 19 The terminal chalcogen atom does, however, influence the geometry around nitrogen as observed from the ~15 o increase in the C4-N-C3 bond angle upon replacing oxygen with sulfur. The increased angle around nitrogen in allyl-NCS is accompanied by a decrease in the C4-N and N-C3 re bond lengths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the previously reported geometries of phenyl-NCO and phenyl-NCS which found no differences in the electronic structure of the ring backbone despite the possibility of a change in πdelocalization of the ring with added -NCO or -NCS substituents. 19 The terminal chalcogen atom does, however, influence the geometry around nitrogen as observed from the ~15 o increase in the C4-N-C3 bond angle upon replacing oxygen with sulfur. The increased angle around nitrogen in allyl-NCS is accompanied by a decrease in the C4-N and N-C3 re bond lengths.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the geometries of HCCNCO 17 and HCCNCS, 18 for example, have shown that changing from oxygen to sulfur results in an increase in the CNC bond angle from 140.7º to 180º. In the phenyl (Ph) containing analogues, 19 the difference in the CNC bond angle increases by a smaller amount (~10º) from 135.2º in PhNCO to 145.1º in PhNCS which is related to a change in the hybridization at nitrogen from a ~sp 1.6 -to a ~sp-hybridized orbital in these two compounds, respectively. Exploring related pairs of compounds with different R groups will provide greater insight into the role of the R substituent and terminal chalcogen on the electronic structures of NCO/NCS-containing species.…”
Section: Introductionmentioning
confidence: 99%
“…This fact makes the above-mentioned mechanism plausible in the condition of excess alcohol. On the other hand, isocyanates also have potential to form associates due to its large permanent electric dipole moment (|μ tot,MP2/aug-cc-pVTZ | = 2.78 D [17], |μ tot,MW | = 2.81 D [18]). Indeed, Lenzi et al reported interaction energy of 24.3–32.8 kJ/mol for alkyl-isocyanates dimers using density functional theory (DFT) calculation [19]; therefore, these isocyanate associates can also be formed in isocyanate excess and can provide a starting point for urethane formation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been significant experimental research progress on substituted isocyanate molecules including substituents such as, -CN, 1 -ClSO 2 , 2 -CCH, 3,4 CH 3 , 5,6 -Ph, 7,8 -CH 2 CH 2 Cl, 9 -t-Bu, 10 and many more [11][12][13][14] Isocyanic acid (HNCO) is the lowest energy isomer of the HNCO system and the simplest isocyanate, 15,16 an important class of molecules for many diverse chemical contexts. HNCO is an atmospheric pollutant formed via the burning of fossil fuels, cigarette use, and other secondary sources.…”
Section: Introductionmentioning
confidence: 99%
“…Cl, and CN) consists of larger substituents that are more relevant to industrial applications. 3,7,8 Three important autocatalyitc mechanisms (RNCO+2 H 2 O, RNCO+3 H 2 O, and H 2 O+2 RNCO) are characterized considering a smaller subset of the aforementioned substituents. The influence of these substituents on their efficiency is systematically studied for the first time.…”
Section: Introductionmentioning
confidence: 99%